On the role of tropopause folds in summertime tropospheric ozone over the eastern Mediterranean and the Middle East - D. Akritidis; D. Akritidis; A. Pozzer; P. Zanis; E. Tyrlis; B. Škerlak; M. Sprenger; J. Lelieveld; J. Lelieveld (Atmospheric Chemistry and Physics, 2016)
We study the contribution of tropopause folds in the summertime pool of tropospheric ozone over the eastern Mediterranean and the Middle East (EMME) with the aid of the ECHAM5/MESSy Atmospheric Chemistry (EMAC) model. Tropopause fold events in EMAC simulations were identified with a 3-D labeling algorithm that detects folds at grid points where multiple crossings of the dynamical tropopause are computed. Subsequently the events featuring the largest horizontal and vertical extent were selected for further study. For the selection of these events we identified a significant contribution of the stratospheric ozone reservoir to the high concentrations of ozone in the middle and lower free troposphere over the EMME. A distinct increase of ozone is found over the EMME in the middle troposphere during summer as a result of the fold activity, shifting towards the southeast and decreasing altitude. We find that the interannual variability of near-surface ozone over the eastern Mediterranean (EM) during summer is related to that of both tropopause folds and ozone in the free troposphere.